Parametric Optimization of a Rod Subject to Forced Torsional Vibratiom - Foryś, A.S. (Engineering Transactions, 1992)
Forced torsional vibration of a rod madeof a Kelvin-Voigt viscoelastic material is analyzed. The rod has the form of a truncated cone. One end of the rod is loaded by a harmonically variable torque, the other end is rigidly fixed. Vibrational amplitude of the cross-section subject to external excitation is the objective function its minimum determines the optimum shape of the rod. The results derived are based on the solution consisting of the first term of its expansion due to the Galerkin method; the results are illustrated by graphs.